2021
DOI: 10.1007/s10067-021-05580-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-phospholipids antibodies and immune complexes in COVID-19 patients: a putative role in disease course for anti-annexin-V antibodies

Abstract: Introduction Besides distinctive respiratory and digestive hallmarks, COVID-19 has been recently associated with a high prevalence of pro-inflammatory and hypercoagulable states known as “COVID-19 Associated Coagulopathy” (CAC), corresponding to a worsening in patients’ conditions, whose causes are still to be elucidated. A link between anti-phospholipid antibodies (aPLs) and viral infections has long been suggested. APLs are assessed for anti-phospholipid syndrome (APS) diagnosis, characterized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
17
1
2
Order By: Relevance
“…Misdirected, or defective IFN I responses were reported as a key factor for inefficient immune responses in patients with COVID-19 ( 13) , ( 14) , (15). Moreover, exuberant B-cell responses were regularly found in COVID-19 ( 36) , (37), along with a high prevalence of antiphospholipid- (38), anti-Ro/La- (39)or anti-annexin-V-antibodies (40). It is noteworthy that PGRN-autoantibodies were first identified in plasma from patients with different forms of primary small vessel vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Misdirected, or defective IFN I responses were reported as a key factor for inefficient immune responses in patients with COVID-19 ( 13) , ( 14) , (15). Moreover, exuberant B-cell responses were regularly found in COVID-19 ( 36) , (37), along with a high prevalence of antiphospholipid- (38), anti-Ro/La- (39)or anti-annexin-V-antibodies (40). It is noteworthy that PGRN-autoantibodies were first identified in plasma from patients with different forms of primary small vessel vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, as a limit to their analysis, they acknowledged that the LA test was not performed given lack of access to fresh plasma samples. When considering solid-phase aPL assays, methods that are in principle insensitive to anticoagulation and other confounding agents, the presence of aPL in patients with COVID-19 was recently reported in a handful of case reports and small cohorts of patients ( 7 , 8 ). While encouraging, these data are limited and its interpretation remains controversial, with some investigators proposing an important role of aPL in COVID-19 patients ( 7 , 8 ) while others suggesting no association between aPL and thrombotic events ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies identified a statistical difference in thrombotic risk for aPL-positive versus aPL-negative patients or substantial aPL positivity in their thrombosis cohorts (LA only 45,50 ), 55,[57][58][59]63 whereas most did not. 31,[41][42][43][44][47][48][49]52,54,56,61,62,64,[69][70][71][72]74,75 There are many potential confounders to consider, and it is unlikely that such confounders were considered in all published comparisons. Thus, transient aPL positivity may develop in the sickest patients, who will then be most at risk of thrombosis, and therefore aPL may just reflect an association with, rather than be responsible for, the pathophysiological events.…”
Section: Does Apl Positivity In Covid-19 Reflect a Risk Factor For Thrombosis?mentioning
confidence: 99%